Induction of dwarfing in bougainvillea cv Mahara by use of growth regulators - JAIN, RITU; JANAKIRAM, T; SWAROOP, KISHAN; KUMAWAT, G L (The Indian Journal of Agricultural Sciences, 2014)
Bougainvillea (Bougainvillea spectabilis) is a very popular evergreen landscape plant in tropical and subtropical areas. Because of the vigorous growth habit, bougainvillea needs a lot of labor-intensive pruning when being used as a potted plant. PGRs could be alternatives to frequent pruning on bougainvillea to reduce labor costs. But, little research has been carried out on the use of plant growth retardants (PGRs) for controlling the growth and flowering. The present investigations were carried out to study the effect of growth regulators mainly; paclobutrazol, daminozide and maleic hydrazide on bougainvillea cv Mahara to induce dwarfing. The experiment was laid out in completely Randomized Block Design with 11 treatments and four replications. The rooted cuttings of bougainvillea were planted on 7 July 2012 in earthen pot (10” diameter) containing potting media consisting of sand: soil: FYM in a ratio of 1:2:1. The plants were pruned to a uniform height of 10+2 inches on 3rd September 2012. The growth regulators were applied in the form of foliar spray or drench and data was recorded for vegetative and flowering traits. After 14 weeks, it was observed that there was a significant reduction in plant height and plant spread when paclobutrazol was applied in the form of spray or drench. However, application of maleic hydrazide inhibited the plant growth, on the contrary increased plant height and plant spread over control (Distilled water spray) was observed with 5000 ppm Daminozide (B-9) application. Drench application of paclobutrazol @30 ppm resulted in highest flower index as compared to other treatments.